Juridical Analysis of Fraud and Illegal Banking Practices in Cooperative Operations: A Case Study on the Baitul Mal Wa Tamwil (BMT) Muamaroh Anyer Cooperative - Andre Scondery; Novianti Dasma Putri (Rechtsvinding, 2026)
The Baitul Mal wa Tamwil (BMT) Muamaroh Anyer Cooperative is one of the Islamic financial entities that in practice is suspected of carrying out activities that deviate from the provisions of positive law in Indonesia. This cooperative collects public funds extensively, promises high returns, and conducts savings and loan activities with a system that resembles banking, even though it does not have an operational license from the Financial Services Authority (OJK) or Bank Indonesia. This phenomenon poses serious problems in the realm of criminal law and financial law because it has the potential to harm the public and violate the principle of prudence in the financial industry. The illegal financial practice under the guise of cooperatives also shows the weak legal and financial literacy of the community and the lack of supervision of non-bank financial institutions that use the name of sharia cooperatives. This study aims to analyze juridically the practice of fundraising by BMT Muamaroh Anyer without the permission of official authorities, examine the legal liability of cooperative administrators who are suspected of committing fraudulent crimes, and formulate legal remedies and preventive measures in protecting the community against illegal financial practices. The research uses a normative juridical method combined with an empirical approach through interviews with cooperative administrators and victims who have experienced losses. Primary data sources are obtained from the results of interviews and field observations, while secondary data comes from relevant laws and regulations, legal literature, and academic journals. The analysis was carried out in a qualitative descriptive manner by interpreting field findings based on the applicable legal framework, especially referring to Law Number 10 of 1998 concerning Banking, Law Number 21 of 2011 concerning the Financial Services Authority, Law Number 25 of 1992 concerning Cooperatives, and Article 378 of the Criminal Code concerning fraud. The results of the research are expected to contribute to strengthening the supervision of cooperative-based microfinance institutions, increase public legal awareness, and become the basis for the formulation of stricter policies against cooperatives that deviate from sharia principles and national banking regulations. The outputs of this research are in the form of scientific articles in accredited legal journals, recommendations for cooperative supervision policies, and community legal education through Community Service (PKM) activities. Thus, this research not only has academic value, but also has a direct impact on law enforcement efforts and community protection from illegal financial practices under the guise of cooperatives.